Investigate The Effectiveness Of Google Translate Among Iraqi Students - S. Habeeb, Luwatha (Opción, 2019)
Technology has been proved to be effective in helping the students to improve their English language through the use of various applications. The purpose of the study `is to investigate the effectiveness of Google Translate. The study also investigates the students’ attitudes towards the use of Google Translate. Lastly, the study explored the advantages and disadvantages of Google Translate. The par- ticipants of the study were 50 Iraqi undergraduate students in the studying year 2018/2019 participated in the study. A quantitative research design approach will be adapted to analyse the data gathered from the subjects. The study used a survey questionnaire to collect data from participants. The findings of the study showed that the Iraqi Undergraduate students hold high level of attitude towards the use of Machine Translation (Google Translate). The results have also revealed that Goog- le Translate have some advantages (low cost, easy to access, quick translation) and drawbacks (grammatical mistakes, no proofread tool, etc).